Correlating Atom Probe Tomography with Atomic-Resolved Scanning Transmission Electron Microscopy: Example of Segregation at Silicon Grain Boundaries. (20th February 2017) - Stoffers, Andreas; Barthel, Juri; Liebscher, Christian H.; Gault, Baptiste; Cojocaru-Mirédin, Oana; Scheu, Christina; Raabe, Dierk
Abstract: In the course of a thorough investigation of the performance-structure-chemistry interdependency at silicon grain boundaries, we successfully developed a method to systematically correlate aberration-corrected scanning transmission electron microscopy and atom probe tomography. The correlative approach is conducted on individual APT and TEM specimens, with the option to perform both investigations on the same specimen in the future. In the present case of a Σ9 grain boundary, joint mapping of the atomistic details of the grain boundary topology, in conjunction with chemical decoration, enables a deeper understanding of the segregation of impurities observed at such grain boundaries.